Kreativitas Guru Pendidikan Agama Islam dalam Mendesain Pembelajaran Berbasis Digital - Nafhatul Mawardah (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2021)
This research departs from an educational dynamic which shows that there have been many changes in learning devices due to the pandemic. Learning that was originally done in a simple or manual way has now changed a lot with the touch of digital devices. In addition, another fact that supports the conduct of this research is the selection of the SMPN 1 Kedungpring school as the first digital school in the Lamongan Regency area. This study uses a qualitative method with a descriptive approach. The subjects of this research include principals and teachers. Data collection techniques through observation, interviews, and documentation. Data analysis techniques with data collection, data reduction, data presentation, verification, and drawing conclusions. The results of this study indicate that; (1) creative teachers present PAI material by using imaginative concepts, stimulating ideas and works and applying direct evaluation, applying learning methods by combining existing methods, developing learning media, using digital media in the form of whatsapp, facebook, instagram, youtube, google class room, (2) the challenge of using digital-based learning is to keep abreast of social media developments and to remain consistent in using digital-based learning media.